2015
DOI: 10.1108/tpm-10-2014-0055
|View full text |Cite
|
Sign up to set email alerts
|

Being open matters: the antecedents and consequences of cross-understanding in teams

Abstract: Purpose – The aim of the current paper is to explore the role of cross-understanding as a mediator between openness to cognitive experience and reflective communication cognitions on the one hand and team performance on the other hand using the input-mediator-output-input (IMOI) model as a framework (Ilgen et al., 2005). Design/methodology/approach – The sample consisted of 156 participants organized in 37 student teams. Two mediation mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 52 publications
3
20
0
Order By: Relevance
“…Cross-understanding is a relatively new concept in team cognition literature and the empirical evidence of its benefits on team performance is very little. To our knowledge there is only one paper that investigated the role of cross-understanding (Meslec & Graff, 2015). Answering their call we investigate the role of cross-understanding in other relation and in organizational setting: transactional leadership and adaptive performance.…”
Section: Discussionmentioning
confidence: 99%
“…Cross-understanding is a relatively new concept in team cognition literature and the empirical evidence of its benefits on team performance is very little. To our knowledge there is only one paper that investigated the role of cross-understanding (Meslec & Graff, 2015). Answering their call we investigate the role of cross-understanding in other relation and in organizational setting: transactional leadership and adaptive performance.…”
Section: Discussionmentioning
confidence: 99%
“…Higher levels of crossunderstanding in a team is theorized to positively influence the way in which teams present, assimilate, and utilize knowledge. Empirical research on cross-understanding is still emerging, but the available evidence from published studies (Meslec & Graff, 2015;Otoiu, Andrei, & Băban, 2012) and conference presentations (Bayer & Lewis, 2013;Lewis & Herndon, 2015;Rariden & Lewis, 2013) suggests that teams with higher cross-understanding perform at higher levels as theorized. The current study adds to this literature with a large-scale empirical investigation of not only the effects of cross-understanding on team performance, but also its effects on individual performance (Huber & Lewis, 2010), which has not yet been examined.…”
Section: Getting To Know You: Motivating Cross-understanding For Imprmentioning
confidence: 99%
“…Although quantitative research on cross-understanding is still emerging, a recent study by Meslec and Graff (2015) demonstrated that cross-understanding positively affects team performance. Examining student teams engaged in complex research projects in organizations, Meslec and Graff (2015) showed that teams with low cross-understanding are unable to utilize diverse perspectives, and therefore perform worse than their higher cross-understanding counterparts. In accordance with the theoretical predictions and emerging empirical support for the team-level benefits of cross-understanding, we hypothesize the following:…”
Section: Cross-understanding and Team Performancementioning
confidence: 99%
See 2 more Smart Citations